The Relationship Between Self-Concept and Deception Behavior in Social Media Users at International College X - Ifana, Anisa (Lafadz Jaya Publisher, 2025)
This study aims to determine the relationship between self-concept and deception behavior in social media users at International College X. The population in this study were students at International College X totaling 86 people. The method used for sampling to be used in the study was saturated sampling (census). The results of the validity test of deception behavior on the scale obtained 22 items that met the criteria as valid items and 10 items were declared invalid from a total of 32 items. The self-concept scale obtained 22 items that met the criteria as valid items and 14 items were declared invalid from a total of 36 items. Based on the results of the analysis of research data to test the hypothesis, the r value was obtained as 0.938 and the p value was 0.000, meaning p <0.05, this means that there is a relationship between self-concept and deception behavior in social media users at International College X. So it can be concluded that there is a positive relationship between self-concept and deception behavior in social media users at Jakarta International College.